115k views
2 votes
FAST!!!!!!!!!!!!
I prefer the better answer though.

FAST!!!!!!!!!!!! I prefer the better answer though.-example-1
User Squirly
by
5.0k points

1 Answer

6 votes

Answer:

The answer to your question is: ( -10, 9)

Explanation:

Equations given - 8x - 9y = -1

y = 9

Substitute "y" in the first equation

- 8x - 9(9) = -1

- 8x - 81 = - 1

- 8x = 81 - 1

- 8x = 80

x = 80 / -8

x = -10

Point ( - 10, 9)

User GoraKhargosh
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.